1996
DOI: 10.1021/la950289b
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Monolayers of Tetraethylene Glycol Monododecyl Ether Adsorbed on Self-Assembled Monolayers on Silicon:  A Neutron Reflectivity Study

Abstract: We have used neutron reflection to study, for the first time, the structure of a surfactant layer adsorbed at the hydrophobic solid/water interface. Isotopic labeling of the water and of the hydrophobic selfassembled layer of octadecyltrichlorosilane (OTS) was first used to characterize protonated and deuteriated hydrophobic layers on the silicon oxide on the (111) face of silicon. This is the first time the structure and composition of such layers has been examined under water. Some water penetration into bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
118
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(143 citation statements)
references
References 30 publications
24
118
1
Order By: Relevance
“…On the other hand, with the UV-ozone treatment the oxide layer was surprisingly good: low value of thickness and great homogeneity. We systematically looked for water contamination, which is usually found in oxides grown in aqueous solutions [10], but did not detect any. The same silicon blocks, without lipids, have been investigated in four water contrasts [13]: all results indicate the same roughness, thickness and homogeneity of oxide.…”
Section: Structure Of the Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, with the UV-ozone treatment the oxide layer was surprisingly good: low value of thickness and great homogeneity. We systematically looked for water contamination, which is usually found in oxides grown in aqueous solutions [10], but did not detect any. The same silicon blocks, without lipids, have been investigated in four water contrasts [13]: all results indicate the same roughness, thickness and homogeneity of oxide.…”
Section: Structure Of the Layersmentioning
confidence: 99%
“…A bilayer suspended in water is stable but position control is not sufficient for reflectivity measurements. The solution consists in grafting lipid layers on silicon [10], or physically adsorbing them on a hydrophilic oxide [11]. This allows an in-situ, non destructive investigation of thickness, roughness, hydration, fluctuations and composition of phospholipid bilayers in a liquid medium, as well as their interaction with proteins.…”
Section: Introductionmentioning
confidence: 99%
“…However, in practice it is much more important to maximize the reflected signal from the protein layer. We have demonstrated previously that the use of deuterated octadecyltrichlorosilane (d-OTS) can highlight the adsorbed protein substantially (28). The origins of this enhancement are not simple to explain but lie partly in the very high scattering length density of the densely packed OTS layer and the generation of strong interference in the reflectivity from the composite layer of OTS and protein.…”
Section: Neutron Reflection and Contrast Variationmentioning
confidence: 99%
“…[1][2][3] In particular, efforts have been directed to the investigation of conformational changes undergone by the protein molecules upon adsorption using a variety of techniques including ellipsometry, 4,5 neutron reflection, [6][7][8] circular dichroism, 2 Fourier Transform InfraRed Spectroscopy in the Attenuated Total Reflection mode (FT IR-ATR), [9][10][11][12] and differential scanning calorimetry. 13,14 Also of considerable interest are any structural changes undergone by a pre-adsorbed protein layer under external factors, as the heating and the displacement by small molecules.…”
mentioning
confidence: 99%
“…The value of concentration is consistent to the values found by other authors, and as found in these studies, was slightly below in maximally dense mono-layer. 7,8 The hydrophilic surfaces were prepared by performing the RCA 1 standard cleaning procedure at 75 C, as described in our previous papers. 4,6 The silicon oxide layers were characterised by ellipsometry and the average measured thickness was 14 AE 4 # A. Ellipsometry measures the changes in polarisation of an electromagnetic wave reflected from the experimental system, and has been thoroughly described in other works.…”
mentioning
confidence: 99%